Stability of extemporaneously prepared sitagliptin phosphate solution - Zaid, Abdel Naser; Abu Zaaror, Yara; Kaddumi, Aiman; Ghanem, Mashhour; Jaradat, Nidal; Abu Salah, Tharaa; Siaj, Sameera; Omari, Lana (PLOS ONE, 2022)
Sitagliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor that is used orally in conjunction with diet and exercise to control sugar levels in type 2 Diabetes Mellitus patients. This study aimed to extemporaneously prepare SiP solution (1% w/v) using pure Sitagliptin phosphate (SiP) powder and assess its stability according to pharmaceutical regulatory guidelines. Four SiP solutions, coded T1, T2, T3, and T4, were extemporaneously prepared using pure SiP powder as a source of API. The most suitable one, in terms of general organoleptic properties, was selected for further investigations, including stability studies. For this last purpose, samples of the T4 solution were kept under two storage conditions, room temperature (25˚C and 60% Relative Humidity) and accelerated stability conditions (40˚C and 75% Relative Humidity). Assay, pH, organoleptic properties, related substances, and microbial contamination were evaluated for 4 consecutive weeks. A High-Performance Liquid Chromatography (HPLC) analytical method was developed and validated to be used for the analysis and quantification of SiP in selected solution formulation. The adopted formula had a pH on the average of 3 to 4. During the stability tests, all pH values remained constant. Furthermore, after 4 weeks of storage under both conditions, the SiP concentration was close to 100%. A stable SiP extemporaneous solution was successfully prepared using pure SiP powder. Patients with swallowing problems who use feeding tubes and are unable to take oral solid dosage forms may benefit from this research. Community pharmacists can prepare the solution using sitagliptin powder as the source of the active ingredient.